ANALISIS PREDIKSI FINANCIAL DISTRESS MENGGUNAKAN MODEL ALTMAN Z-SCORE, ZMIJEWSKI, SPRINGATE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Suryaman, Ahmad; Nurhayati, Immas; Yudawati, Diah (prodima@fe.uika-bogor.ac.id, 2017)
The main purpose of this research is to analyze or predict the level of financial distress at PT. Indocement Tunggal Prakarsa Tbk and PT. Astra International Tbk uses several methods namely altman, zmijewski and springate. The annual financial report data used in this study is secondary dataobtained from the Indonesia Stock Exchange. The results showed, when tested using the method of Altman and Zmijewski, the two companies condition are in non-financial distress, but when tested using Springate method, in 2013 – 2016, PT. Astra International Tbk indicated in financial distress condition.